2013 IEEE Congress on Evolutionary Computation 2013
DOI: 10.1109/cec.2013.6557679
|View full text |Cite
|
Sign up to set email alerts
|

Metaheuristics application on a financial forecasting problem

Abstract: EDDIE is a Genetic Programming (GP) tool, which is used to tackle problems in the field of financial forecasting. The novelty of EDDIE is in its grammar, which allows the GP to look in the space of technical analysis indicators, instead of using prespecified ones, as it normally happens in the literature. The advantage of this is that EDDIE is not constrained to use prespecified indicators; instead, thanks to its grammar, it can choose any indicators within a pre-defined range, leading to new solutions that mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…Results showed that all of these meta-heuristics provided significant improvements to the predictive performance of EDDIE-8. Smonou et al [2] also state that the GLS algorithm returned the best performance out of the three, significantly outperforming its opponents. However, a new issue arose, which was the algorithm's computational cost, as the GLS introduced a high number of additional fitness evaluations.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…Results showed that all of these meta-heuristics provided significant improvements to the predictive performance of EDDIE-8. Smonou et al [2] also state that the GLS algorithm returned the best performance out of the three, significantly outperforming its opponents. However, a new issue arose, which was the algorithm's computational cost, as the GLS introduced a high number of additional fitness evaluations.…”
Section: Introductionmentioning
confidence: 95%
“…Due to its importance, an increasing number of investors and researchers have been attracted to investigate in the field [2]- [5]. In recent years, with the latest technological advancements, many financial forecasting tools, which take advantage of computational intelligence, have been released [6].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations